THE RESEARCH ON THE DEMONSTRATION EFFECT: A SURVEY OF THE COALITION FOR CLEAN AND FAIR ELECTIONS (BERSIH) IN MALAYSIA - Jamaluddin Mustaffa; Mohd Hilmi Hamzah; Kamarudin Ngah (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2023)
This study aims to identify the factors that lead and influence participation of community to be involved in street demonstrations. This study also surfaces the effect of the demonstration and the measures suggested by respondents to address the problem of street demonstrations. Methodology of the study is through a survey method using questionnaires in which the samples of 150 respondents from communities in Malaysia are gathered. The results showed that out of the eight claims, the main solution is to put an end to corrupt elections. This is followed by 2) stop dirty politics, 3) clean the list of votes, 4) use of indelible ink, 5) access to free and fair media, 6) strengthen public institutions, 7) the minimum campaign period of 21 days and 8) reforming the postal ballot. The finding also shows that the factors that influence community involvements with street demonstrations is because of the role played by the leaders involved and self-political choice.. Results of the survey also shows that the respondent agrees that demonstration gives impact to the political, economic and social, In summary it can be concluded that the purpose or the main factor community conduct demonstration is because of disagreement with the political leaders and self –political choice in order to stop corrupt elections. Hence the measures proposed by the respondent should be brought forward and heard by certain parties to avoid negative impact to the Country.